Indications of Defects of Consent as Grounds for the Annulment of a Prenuptial Agreement in a Mixed Marriage - Alvina Anandita Rahma (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Mixed marriages between Indonesian nationals and foreign nationals give rise to specific legal complexities, particularly with regard to prenuptial agreements. Differences in language and legal systems between countries have the potential to create defects of consent (wilsgebrek) that undermine the validity of such agreements. This study aims to analyse the forms of defects of consent as grounds for the annulment of prenuptial agreements under Indonesian contract law, and to examine their application in Judgment No. 340/Pdt.G/2017/PA.Amb. The method employed is a normative legal analysis using a statutory approach and a case-based approach. The results of the study indicate that the Civil Code recognises three forms of defects of consent, namely mistake (dwaling), duress (dwang), and fraud (bedrog), which are respectively regulated in Articles 1322, 1323–1327, and 1328 of the Civil Code. In the case under review, there are strong indications of two forms of defects of consent simultaneously: mistake, as the prenuptial agreement was drafted in Japanese, a language the Plaintiff did not understand; and fraud, as the Defendant concealed his marital status. Although the Ambarawa Religious Court only adjudicated the divorce claim, these indications of defects of consent legally provide grounds for the annulment of the prenuptial agreement under Article 1321 of the Civil Code.